Comparative effect of 3 different fix-combination antihypertensive treatments in fasting glucose, fasting insulin, OGTT and HbA1c levels, in prediabetic hypertensive patients. (3rd October 2022) - Liontos, A; Biros, D; Papathanasiou, A; Papagiannopoulos, C; Klouras, E; Veliani, C; Kolios, N G; Pappa, C; Liberopoulos, E; Elisaf, M; Milionis, H; Liamis, G
Abstract: Introduction: The effect of various antihypertensive drugs on the glucose homeostasis has been discussed extensively. Dual combination treatment is advised with current guidelines. We present comparative data of the effect of delapril/manidipine versus valsartan/amlodipine versus telmisartan/amlodipine combination treatments, in fasting glucose, fasting insulin, OGTT and HbA1c levels, before and after the 3-month treatment, in hypertensive prediabetic patients. Methods: Data were collected from 154 patients from the outpatient clinic for patients with lipid disorders, hypertension and diabetes of our hospital, during the period 2014–2018. A number of 53 persons was randomized in the delapril/manidipine group 30/10 mg per day while 51 persons had been randomized in the group of telmisartan/amlodipine 80/5mg per day and 54 patients in the valsartan/amlodipine 160/5 mg per day. All patients successfully completed the study. Baseline characteristics are presented in Table 1A. Results: The resulting alternations in glucose, insulin, OGTT and HbA1c levels, before and after the 3-month treatment are presented on Table 1B for the 3 groups of treatment. Conclusions: In the comparison between the groups, a statistically significant difference was found in the change in INS values from the beginning of treatment until 3 months, for the TEL/AMLO treatment group, where a statistically significant difference from the DEL/MANI treatment group (p-value<0.01) and a strong statistically significant difference from the VAL/AMLO treatment group (p-value<0.001) were noted. The TEL/AMLO group had the only decrease in insulin levels compared to the other treatment groups where an increase was observed, after the treatment. The change in OGTT levels showed a statistically significant difference (p-value<0.05) between the DEL/MANI treatment group (a decrease of 6.63%) compared to the TEL/AMLO treatment group (an increase of 1.53%) after 3 months of treatment. Funding Acknowledgement: Type of funding sources: None.